New Life Prediction Method of the Grease by the Activation Energy - Azusa Ide (Japanese Society of Tribologists, 2011)
This paper proposes a new grease life predicting method which utilizes kinetics analysis of measured data obtained through thermogravimetry. The grease life is predicted by weight loss at a certain temperature. By separating effects of complex dynamics and physics in ball bearings to which the grease is applied, a static life of the grease can be predicted as a stand-alone evaluation within very short period of time.